Do it anyway : don't give up before it gets good - Cobbs-Leonard, Tasha, 1981-; Thrasher, Travis, 1971- (WaterBrook, 2024)
"Tasha tells remarkable stories of experiencing this firsthand when she committed to dreams even when they seemed unrealistic, pursued adoption though it looked impossible, navigated the dynamics of a blended family despite challenges, and watched God move in each step of endurance through infertility and depression"--Amazon.